Integrative taxonomy reveals phenotypic plasticity in the freshwater mussel Contradens contradens (Bivalvia: Unionidae) in Thailand, with a description of a new species. Issue 2 (17th February 2019) - Jeratthitikul, Ekgachai; Phuangphong, Supanat; Sutcharit, Chirasak; Prasankok, Pongpun; Kongim, Bangon; Panha, Somsak
Abstract : The freshwater mussel Contradens contradens (Lea, 1838) occurs in most types of freshwater habitats throughout Thailand. The species shows extensive variation in shell morphology, which has led to the recognition of six different subspecies. In this study, the validity of these six subspecies plus one unknown species was assessed using an integrative taxonomic approach. Geometric morphometric analyses revealed significant differences in shell shapes among these six nominal morphological subspecies, although a considerable degree of overlap was detected in some groups. In contrast, the phylogenetic tree obtained from the concatenated data of mitochondrial COI and nuclear H3 gene sequences and molecular species delimitation analyses revealed only three supported clades. These clades are proposed herein as three distinct species, and strongly corresponded to the biogeographically disjunct drainage systems in Thailand. They consisted of the (i) C. contradens clade found in the Chao Phraya Basin and other rivers that drain into the Gulf of Thailand, (ii) C. crossei clade that is restricted to the Middle Mekong Basin, and (iii) a clade containing only the newly discovered species from Huai Luang River in the north-east of Thailand, which is described herein as Contradens rolfbrandti Jeratthitikul & Panha, sp. nov. Speciation among these congeners was probably caused by the restriction of gene flow due to the past geomorphology of the river systems. The intraspecific variation in the shell shape detected here does not reflect the evolution of the mussel, but rather is evidence of phenotypic plasticity.http://zoobank.org/urn:lsid:zoobank.org:pub:649B6093-E1DD-4FD8-8185-A4696C43AD36 ; http://zoobank.org/urn:lsid:zoobank.org:act:777DDE86-8397-4FF3-AA78-0BE0F34611F4